Surfactant in SARS-CoV-2 - a therapeutic option based on underlying lung cell damage? - Carvalho Sousa, Maristella de Araújo; Matos de Oliveira, Gabriela Correia; de Oliveira Andrade, Luis Jesuino (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: the severe acute respiratory syndrome – coronavirus 2 (SARS Cov-2), leads to a diffuse alveolar deterioration due infection of type II pneumocytes. The type II pneumocytes are involved in synthesis and secretion of pulmonary surfactant in pulmonary alveoli. Objective: the purpose of this study is to discuss the indication of surfactant replacement as a potential adjunctive treatment modality for SARS CoV-2, similarly treatment to neonatal respiratory distress syndrome. Methodology: we argue that SARS can be triggered by surfactant deficiency secondary to production deficiency determined by type 2 pneumocyte injuries. In this sense, we carried out a bibliographic review. Conclusion: thus, the replacement of human surfactant could be a potential treatment modality for SARS CoV-2, in the same way that it is indicated for the treatment of neonatal respiratory distress syndrome